TEACHER'S EFFORT IN OPTIMIZING THE READING ABILITY OF CLASS I STUDENTS THROUGH ONLINE LEARNING - Cucu Suryana; Naila Kurnia Restu; Dede Margo Irianto; Yeni Yuniarti (IKIP Siliwangi, 2022)
This study aims to examine the efforts of teachers in optimizing the reading skill of first grade elementary school students during the pandemic, examine the responses of teachers and parents, and examine the difficulties experienced by teachers and parents in teaching students to read during the pandemic. The research method used is the case study method. The research instruments used were documentation, observation sheets and interviews. The results of this study are the first teacher's efforts in optimizing the reading skill of 1st grade elementary school students during the pandemic is to create a